An image analysis study of pit formation on Ti-6Al-4V - Codaro, E. N.; Nakazato, R. Z.; Horovistiz, A. L.; Ribeiro, LMF; Ribeiro, R. B.; Hein, LRO (Elsevier B.V., 2003)
Metallographic techniques and digital image processing have been used to investigate heat-treated Ti-6Al-4V pitting corrosion, often used as aircraft components. LM and SEM metallography of 'as received', annealed (heating up to 800 degreesC/30 min and cooling furnace) and aged (heating up to 900 degreesC/30 min, quenching in water, heating up to 540 degreesC/240 min and again water-quenched) microstructures reveal pitting sites at primary and secondary alpha/beta interfaces. Microstructural arrangements influence and corrosive environment association on pit morphology could be demonstrated by digital image analysis and results statistical treatment. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: pitting corrosion; pit morphology; titanium alloy; image processing and analysis; shape descriptors; quantitative metallography